Clarifying students' feedback‐seeking behaviour in clinical clerkships. Issue 3 (8th February 2013) - Bok, Harold G J; Teunissen, Pim W; Spruijt, Annemarie; Fokkema, Joanne P I; van Beukelen, Peter; Jaarsma, Debbie A D C; van der Vleuten, Cees P M
<x xml:space="preserve">Abstract</x> Context Why and how do students seek feedback on their performance in the clinical workplace and which factors influence this? These questions have remained largely unanswered in research into workplace learning during clinical clerkships. Research on feedback has focused mainly on feedback providers. Whether and how feedback recipients actively seek feedback are under‐examined issues. Research in organisational psychology has proposed a mechanism whereby feedback seeking is influenced by motives and goal orientation mediated by the perceived costs and benefits of feedback. Building on a recently published model of resident doctors' feedback‐seeking behaviour, we conducted a qualitative study to explore students' feedback‐seeking behaviours in the clinical workplace. Methods Between April and June 2011, we conducted semi‐structured face‐to‐face interviews with veterinary medicine students in Years 5 and 6 about their feedback‐seeking behaviour during clinical clerkships. In the interviews, 14 students were asked about their goals and motives for seeking feedback, the characteristics of their feedback‐seeking behaviour and factors influencing that behaviour. Using template analysis, we coded the interview transcripts and iteratively reduced and displayed the data until agreement on the final template was reached. Results The students described personal and interpersonal factors to explain their reasons for seeking feedback. The factors related to intentions and the characteristics of the feedback provider, and the relationship between the feedback seeker and provider. Motives relating to image and ego, particularly when students thought that feedback might have a positive effect on image and ego, influenced feedback‐seeking behaviour and could induce specific behaviours related to students' orientation towards particular sources of feedback, their orientation towards particular topics for and timing of feedback, and the frequency and method of feedback‐seeking behaviour. Conclusions This study shows that during clinical clerkships, students actively seek feedback according to personal and interpersonal factors. Perceived costs and benefits influenced this active feedback‐seeking behaviour. These results may contribute towards the optimising and developing of meaningful educational opportunities during clerkships.